Effect of bleed air on performance of small turbojet engine used in unmanned aerial vehicle - Aygun, Hakan (Taylor & Francis Inc, 2023)
Being one of the most common gas turbine systems, turbojet engines have been highly preferred in aviation sector owing to their higher thrust to weight ratio and reliability compared with reciprocating engines. To improve turbojet efficiency, a number of analyses have been applied on these systems in both theoretical and practical ways so far. In this study, it is analyzed that how bleed air ratio (BAR) ranging 1% and 8% taken from air compressor affects performance of small turbojet engine (STE) at cruise altitude of 10 km since the BAR is tried to decrease on new technology gas turbine engines. Moreover, influence of Mach number ranging from 0.5 to 0.75 on the STE performance is addressed. According to performance outcomes, as BAR increases up to the highest, net thrust of the turbojet engine decreases from 1.471 kN to 1.303 kN whereas SFC ascends from 35.99 g/kNs to 37.74 g/kNs, which corresponds to 11.42% decrement of thrust and 4.86% increment of SFC. However, the higher Mach leads net thrust and SFC to increase by 13.1% and 2.55%, respectively. Finally, the higher BAR causes environmental effect factor (EEF) of the engine higher from 6.397 to 6.650. However, increasing Mach affects its EEF in a way of enhancement of sustainability, namely the EEF decreases from 7.637 to 5.26. It could be inferred that the higher bleed air ratio compromises the engine performance whereas the higher Mach favorably affects efficiency of energy and exergy, which makes specific fuel consumption higher.
Keywords: Bleed air; exergy efficiency; Mach number; gas turbine; small turbojet; >